Praktik Meditasi Chan di Era Digital: Adaptasi dan Efektivitas Praktik Daring-Luring pada Komunitas Buddha Mahayana di Wihara Ekayana Serpong - Riska Handayani; Syaiful Azmi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2026)
This study aims to describe the practice of Chan Meditation carried out by the Mahayana Buddhist community at Ekayana Serpong Temple, Tangerang Regency, Banten, and to examine its adaptation and effectiveness in the digital era. A qualitative method with a psychology of religion approach was used, involving observation, in-depth interviews with practitioners and community leaders, and documentation of activities. The findings show that Chan Meditation at Ekayana Serpong Temple consists of five core movements: Namaskara, Sitting Meditation, Walking Meditation, Eight Movements of Awareness, and Yoga. Online sessions were held during the Covid-19 pandemic through Zoom and YouTube Live but were discontinued once in-person activities resumed, as they were considered less able to convey collective energy, guidance quality, and spiritual depth compared to offline practice. Digital technology therefore functions only as a temporary supporting medium, a digitally-mediated practice rather than a digital religion, so that the essence and method of Chan Meditation remain preserved.